The use of Common Duckweed (Lemna minor) in the treatment of wastewater from the washing of sisal fiber (Furcraea bedinghausii) (2016)
(Eng) The production of sisal (Furcraea Bedinghausii) represents one of the main sources of income for many families in the different regions of Colombia. In the department of Cauca, around 12,000 families currently reap the rewards of sisal cultivation. Only 4% of the sisal leaf is actually used, the remaining 96% comprising juice and bagasse. Washing the harvested sisal is a stage in the transformation process that contaminates large volumes of water. This goes on to reach a natural water source, in this case the Las Margaritas river in Silvia, Cauca. With the above concern in mind, this study puts forward an alternative solution using Common duckweed (Lemna minor). Evaluation of the efficiency of the phytoremediation process on a pilot scale was carried out through the characterization of such physicochemical parameters as BOD5, COD, TSS, nitrogen and phosphorus in the water. The variable used was hydraulic retention times (HRT), which were eight and twelve days. Results suggest that percentage removal by Lemna minor was highest with a HRT of eight days, reaching values of 79.6 % and 82.77 % for COD and BOD5 respectively.